Proyecto a nivel de ejecución de las oficinas académicas y administrativas de la facultad de Ingeniería Civil - Yaringaño Zevallos, Luis (2005)
Since the creation of the National University of San Martin, there was need to implement the University City, through the Department of works and infrastructure, and in where is comprised the Faculty of Civil Engineering, which is already developed some environments such as classrooms, their hygienic services and their laboratories in its first stage. With the mention of project is intended to complement in part that failure to complete the flat set of the Faculty of Civil Engineering, and within them have the project of the academic and administrative offices which would bring the Faculty in considerable physical progress. Only missing by build the classroom Magna, House of force, services complementary (Cafetín) and them services hygienic and their Lab.oratorios in its second stage and some small access, with their respective gardens, that would be a prototype in joint, that would serve to develop and implement them d...